1975
DOI: 10.1111/j.1365-2338.1975.tb02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Consequences of Cereal Monoculture on Gaeumannomyces graminis (Sacc.) Arx & Olivier and the Take‐all Disease1

Abstract: Studies were made of isolates of Goeumannomyces graminis (Sacc.) Arx & Olivier var. tritici J. Walker from different length crop sequences of wheat and barley following permanent grassland. Studies were done on the influence of crop ping intensity of soils, natural and steam disinfested, on disease expression from added inoculum. Efforts were also made to detect interactions between isolates and soils from the same and different cropping sequences. Investigation of variability in the pathogen related to virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Ggt in vitro aggressiveness was significantly higher for G 2 than for G 1 isolates (Lebreton et al ., 2004). Other studies demonstrated the association between changes in the pathogen in terms of morphological and pathogenicity characteristics and stages in Ggt epidemics (Cunningham, 1975; Bateman et al ., 1997; Chu Chou and Hornby, 1972, cited in Hornby et al. , 1998; Slope and Gutteridge, 1982, cited in Hornby et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ggt in vitro aggressiveness was significantly higher for G 2 than for G 1 isolates (Lebreton et al ., 2004). Other studies demonstrated the association between changes in the pathogen in terms of morphological and pathogenicity characteristics and stages in Ggt epidemics (Cunningham, 1975; Bateman et al ., 1997; Chu Chou and Hornby, 1972, cited in Hornby et al. , 1998; Slope and Gutteridge, 1982, cited in Hornby et al.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in the rhizosphere microbial communities have been shown to occur in soil after successive wheat cropping (Raaijmakers et al ., 1997) or different nitrogen fertilization (Sarniguet et al ., 1992) and contribute to TAD (Cook and Rovira, 1976; Sarniguet and Lucas, 1992; Raaijmakers and Weller, 1998) and soil suppressiveness to the disease (Sarniguet et al ., 1992). But changes in the characteristics of the pathogen itself (Cunningham, 1975; Slope and Gutteridge, 1982) or in Ggt population structure (Bateman et al ., 1997; Lebreton et al ., 2004) have sometimes been associated with the progress of take‐all polyetic epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of highly pathogenic isolates was high in G 2 group but there was no direct correspondence between aggressiveness and genotype. Some studies demonstrated the association between changes in the pathogens in terms of morphological and pathogenicity characteristics and stages in Ggt epidemics (Chu Chou and Hornby, 1971; Cunningham, 1975; Slope and Gutteridge, 1982; Bateman et al ., 1997). Bateman and colleagues (1997) demonstrated that perithecia were produced more abundantly on wheat roots seedlings inoculated with T 1 isolates than with T 2 isolates, which were more frequent before take‐all peaked in wheat sequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, nothing is known about the dynamics of Ggt population structure under the effects of successive wheat crops and increases in populations of antagonistic microflora. One alternative or complementary hypothesis to explain TAD is that the frequency of Ggt weakly aggressive strains could increase during wheat monoculture (Tivoli et al ., 1974; Cunningham, 1975; Slope and Gutteridge, 1982). But, the epidemiological role of changes in Ggt population structure has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a continuous supply of susceptible cereal roots might be the only chance for survival or maintenance of moderately or weakly virulent types. This could account for the observation ot Cunningham (1975) that average virulence tended to decrease slightly but detectably with prolonged culture of wheat or barley in Ireland. Nevertheless, even allowing for lOft moderately or weakly virulent isolates in our tests, the recovery of G. graminis var.…”
Section: Discussionmentioning
confidence: 88%